Precautionary Savings, Loss Aversion, and Risk: Theory and Evidence - Sanjit Dhami; Narges Hajimoladarvish; Konstantinos Georgalos (Center for Economic Studies and ifo Institute (CESifo), 2023)
We consider a simple, two period, consumption-savings model with future income uncertainty that examines the interplay of savings, precautionary savings, loss aversion, and risk. We provide the relevant theory, followed by empirical tests based on subject-specific choices, and the measurement of subject-specific behavioral parameters such as loss aversion and present bias. We predict, and show empirically, that loss aversion reduces savings, and that those who are more loss averse are less likely to engage in precautionary savings. Present-bias reduces savings. We also show that decision makers save more in response to a mean preserving spread of future random incomes, and this response is strengthened by loss aversion. We term this as the loss aversion-hedging motive.
Keywords: D01; D91; 330; income uncertainty; precautionary savings; loss aversion; loss aversion-hedging